Behind forest cover changes: is natural regrowth supporting landscape restoration? Findings from Central Italy. (4th May 2018) - Marchetti, Marco; Vizzarri, Matteo; Sallustio, Lorenzo; di Cristofaro, Marco; Lasserre, Bruno; Lombardi, Fabio; Giancola, Carmen; Perone, Annalisa; Simpatico, Annamaria; Santopuoli, Giovanni
Abstract: In recent years, depopulation and abandonment of traditional practices in the mountainous areas have affected the land use and land cover inducing the modification of the landscape mosaic. These processes have consequently facilitated the forest expansion, sometimes altering the floristic composition of the original vegetation in forests and other wooded lands. Forest expansion processes modified the structure, the stand density and the regeneration capacity of forests, thus altering the ecosystems' functionality and resilience. These processes can be considered as a form of landscape degradation, which represents an emerging and common issue in the Mediterranean mountainous ecosystems. This study presents an overview of the main landscape dynamics occurring in the last two decades in the "Collemeluccio-Montedimezzo Alto Molise" Man and Biosphere Reserve, located in Central Italy. The results here obtained deeply describe the main effects induced by forest cover changes, such as those related to the crown coverage dynamics-biodiversity linkages, offering a valuable contribution to improve the management and planning in these situations widely replicable to similar contexts.